P‐1.12: 5T2C Hybrid Compensation Circuit for AMOLED Displays. (28th November 2018) - Wu, Xiaoling; Han, Baixiang; Nie, Chenglei; Cai, Yuying; Chaw, Gary
Abstract : We introduce a novel pixel circuit for active matrix‐organic light emitting diode (AMOLED) displays. This pixel circuit is a kind of hybrid compensation method with both internal compensation and external compensation, wherein the pixel circuit includes five n‐type thin‐film transistors (TFTs) and two capacitors (5T2C) as well as an organic light‐emitting diode (OLED). In this kind of hybrid compensation, the external compensation extracts the threshold voltage of the driving TFT during the turning on or turning off period of the TV. Once the threshold voltage is extracted, they can be used during the internal compensation procedure. By simulating the pixel circuit using this hybrid compensation method, we confirm that the pixel circuit can compensate the panel stability by internal compensation and the whole panel uniformity by external compensation due to the shift of the threshold voltage of the driving TFT.